Impact of Knowledge Management Infrastructure on Academic Staff Effectiveness: An Empirical Study at the University of Jordan - Mikkawi, Balsam; Masadeh, Raed; AlLozi, Musa (Jordan Journal of Business Administration, 2017)
The aim of this research is to explore the impact of knowledge management infrastructure (information and communication technology, organizational culture and organizational structure) on the effectiveness of academic staff at the University of Jordan. A total of 316 questionnaires were used to analyze information from the respondents. Results of the current study revealed that there is a significant positive impact of KM infrastructure on academic staff effectiveness. Also, the study found that there are statistically significant differences in the impact of knowledge management infrastructure on academic staff effectiveness due to academic rank. The researchers recommend the University to ensure the existence of KM infrastructure and implement knowledge sharing among its academic staff.